The Principle of Judicial Cooperation New Code of Civil Procedure: An Analysis Protection from the Worker Front of the Institute of Judicial Recovery - Bega, Patricia Fernandes (2016)
The article is subject to study the Principle of Judicial Cooperation. The problem of research focuses on the conflict between the institution of bankruptcy and labor laws. The initial hypothesis is that the principle of protection to workers and the Judicial Recovery Institute reveal clash, contradiction and non-cooperation. In this way, the work seeks to demonstrate that the procedural rule of judicial cooperation brought about by the new CPC is an instrument of dialogue between material contradictions. The objective is to analyze the new civil procedure code and the difficulty to cooperate the irreconcilable. The method used was deductive.